Determinan Permintaan Jasa Transportasi Ojek Online di Kota Pekanbaru - Intan Tsalasa Yuningsih; Mardiana Mardiana; Yanti Mayasari Ginting (Pusat Riset dan Inovasi Nasional, 2026)
This study was conducted to analyze the effects of price, income level, and travel distance on the demand for online motorcycle taxi services in Pekanbaru. The study employed a quantitative approach using primary data obtained through a questionnaire distributed to online motorcycle taxi users. The sample consisted of 100 respondents selected using quota sampling. Data analysis was performed using multiple linear regression with natural logarithmic (ln) transformation, supported by tests of classical assumptions and hypothesis testing via the t-test, F-test, and coefficient of determination (R²). The results indicate that price has a positive and significant effect on the demand for online motorcycle taxi services. Income has a positive but insignificant effect, while travel distance has a negative and significant effect on demand. Collectively, price, income, and travel distance were found to influence the demand for online motorcycle taxi services. The Adjusted R² value of 0.873 indicates that 87.3% of the variation in demand can be explained by these three variables, while the remainder is influenced by other factors outside the research model.